Genetic variability and phylogeographical patterns of a nonindigenous species invasion: a comparison of exotic vs. native zebra and quagga mussel populations - Stepien, C. A.; Taylor, C. D.; Dabrowska, K. A. (Journal of evolutionary biology, 2002)
There have been few investigations of the number of founding sources and amount of genetic variability that lead to a successful nonindigenous species invasion, although genetic diversity is believed to play a central role. In the present study, population genetic structure, diversity and divergence patterns were analysed for the zebra mussel Dreissena polymorpha [n=280 samples and 63 putative randomly amplified polymorphic DNA (RAPDs) gene loci] and the quagga mussel D. bugensis (n=136 and 52 loci) from 10 nonindigenous North American and six Eurasian sampling sites, representing their present‐day ranges. Results showed that exotic populations of zebra and quagga mussels had surprisingly high genetic variability, similar to those in the Eurasian populations, suggesting large numbers of founding individuals and consistent with the hypothesis of multiple colonizations. Patterns of genetic relationships indicate that the North American populations of D. polymorpha likely were founded by multiple source populations from north‐western and northcentral Europe, but not from southcentral or eastern Europe. Sampling areas within North America also were significantly divergent, having levels of gene flow and migration about twice those separating long‐established Eurasian populations. Samples of D. bugensis in Lakes Erie and Ontario were significantly different, with the former being more closely related to a native population from the Dnieper River, Ukraine. No evidence for a founder effect was discerned for either species.